Common mechanisms of executive attention underlie executive function and effortful control in children. Issue 3 (26th November 2019) - Tiego, Jeggan; Bellgrove, Mark A.; Whittle, Sarah; Pantelis, Christos; Testa, Renee
Abstract: Executive Function (EF) and Effortful Control (EC) have traditionally been viewed as distinct constructs related to cognition and temperament during development. More recently, EF and EC have been implicated in top‐down self‐regulation ‐ the goal‐directed control of cognition, emotion, and behavior. We propose that executive attention, a limited‐capacity attentional resource subserving goal‐directed cognition and behavior, is the common cognitive mechanism underlying the self‐regulatory capacities captured by EF and EC. We addressed three related questions: (a) Do behavioral ratings of EF and EC represent the same self‐regulation construct? (b) Is this self‐regulation construct explained by a common executive attention factor as measured by performance on cognitive tasks? and (c) Does the executive attention factor explain additional variance in attention deficit hyperactivity disorder (ADHD) problems to behavioral ratings of self‐regulation? Measures of performance on complex span, general intelligence, and response inhibition tasks were obtained from 136 preadolescent children ( M = 11 years, 10 months, SD = 8 months), along with self‐ and parent‐reported EC, and parent‐reported EF, and ADHD problems. Results from structural equation modeling demonstrated that behavioral ratings of EF and EC measured the same self‐regulation construct. Cognitive tasks measured a common executive attention factor that significantly explained 30% of the variance in behavioral ratings of self‐regulation. Executive attention failed to significantly explain additional variance in ADHD problems beyond that explained by behavioral ratings of self‐regulation. These findings raise questions about the utility of task‐based cognitive measures in research and clinical assessment of self‐regulation and psychopathology in developmental samples. Abstract : A common executive attention construct, measured using cognitive assessments of working memory capacity, response inhibition, and general intelligence, explained 30% of the variance in behavioral ratings of self‐regulation, as measured by self‐ and parent‐reported effortful control and parent‐reported executive function. Task‐based measures of executive attention failed to explain statistically significant additional variance in the severity of parent‐reported attention deficit hyperactivity disorder problems to that explained by behavioral ratings of self‐regulation.